Immunogenicity and safety following a homologous booster dose of a SARS-CoV-2 recombinant spike protein vaccine with Matrix-MTM adjuvant (NVX-CoV2373) versus a primary series in people living with and without HIV-1 infection in South Africa: A randomized crossover phase 2a/2b trial - Vivek Shinde; Anthonet Lombard Koen; Zaheer Hoosain; Moherndran Archary; Qasim Bhorat; Lee Fairlie; Umesh Lalloo; Mduduzi S. L. Masilela; Dhayendre Moodley; Sherika Hanley; Leon Frederik Fouche; Cheryl Louw; et al. (Human Vaccines & Immunotherapeutics)
COVID-19 remains a global public health issue and an improved understanding of vaccine performance in immunocompromised individuals, including people living with HIV (PLWH), is needed. Initial data from the present study’s pre-crossover/booster phase were previously reported. This phase 2a/b clinical trial in South Africa (2019nCoV-501/NCT04533399) revisits 1:1 randomly assigned HIV-negative adults (18–84 years) and medically stable PLWH (18–64 years) who previously received two NVX-CoV2373 doses (5 μg recombinant Spike protein with 50 μg Matrix-M™ adjuvant) or placebo. During the 6-month blinded crossover/booster phase, NVX-CoV2373 recipients could receive a single NVX-CoV2373 booster dose and placebo recipients a 2-dose NVX-CoV2373 primary series. NVX-CoV2373 safety and immunogenicity were assessed according to prior SARS-CoV-2 infection and HIV status. Post-crossover, 1900/3793 NVX-CoV2373 recipients were assigned another dose, and 1893/3793 placebo recipients were assigned NVX-CoV2373 primary series. Approximately 56% of the participants were SARS-CoV-2–seropositive (“seropositive”) at crossover (6% PLWH). In seropositive participants (HIV-negative and PLWH), booster-dose anti-spike IgG, MN50 and hACE2 inhibition responses increased to similar levels, exceeding those in seronegative participants. In primary-series and booster cohorts, seronegative PLWH showed higher neutralizing responses (4.9- to 5.5-fold, respectively) versus peak pre-crossover primary-series responses. The safety profile was similar among the pre-crossover/booster phase groups; solicited and unsolicited adverse events were infrequent in all groups. A single NVX-CoV2373 booster dose substantially increased antibodies. All baseline seropositive participants showed higher immune responses than seronegative participants. These findings support use of NVX-CoV2373, including in immunocompromised individuals.